Effect of space charge on the negative oxygen flux during reactive sputtering. (14th February 2017) - Moens, F; Kalvas, T; Van Steenberge, S; Depla, D
Abstract: Negative ions often play a distinctive role in the phase formation during reactive sputter deposition. The path of these high energetic ions is often assumed to be straight. In this paper, it is shown that in the context of reactive magnetron sputtering space charge effects are decisive for the energetic negative ion trajectories. To investigate the effect of space charge spreading, reactive magnetron sputter experiments were performed in compound mode with target materials that are expected to have a high secondary ion emission yield (MgO and CeO2 ). By the combination of energy flux measurements, and simulations, a quantitative value for the negative oxygen ion yield can be derived.